Inhibitory Activity Evaluation of Two Medicinal Plant Extracts (Rosmarinus officinalis & Alhagi maurorum) against Adult of Tribolium Castaneum - Meison Abdulbary (Journal of Global Pharma Technology, 2016)
Medicinal plants (Rosmarinus officinalis and Alhagi maurorum) alcoholic extracts inhibitory effect against Tribolium castaneum adults were examined with concentrations 50, 75 and 100 mg/ml through 24, 48 and 72 hours respectively. The total results indicate that the two plants can be used as insecticides for T. castaneum. However ,The results indicated a significant difference between the two plants in the adult mortality rate, where were adults mortality rate of treatment with plant extract Alhagi maurorum (2.37) in contrast to the plant Rosmarinus officinalis which amounted to (1.19) after 72 hours of treatment. The results showed non-significant differences between concentrations of the plant extract Rosmarinus officinalis in the adult mortality Tribolium castaneum in 24 and 48 hours , while there was a significant difference between concentrations in 72 hours where was the adult mortality rate 5.67 with concentration 100 mg/ml and 1 with concentration 50 and 75 mg/ml respectively. In addition, there were significant differences with extract of Alhagi maurorum between the concentrations in the adult mortality rate at 24 and 48 hours, but the results showed significant differences between the concentrations of the extract in 72 hours reaching 1.33, 4.33 and 5.67 respectively with the concentrations 50, 75 and 100 mg/ml respectively. Keywords: Rosmarinus officinalis, Alhagi maurorum, Tribolium castaneum.